Islamic Thought and Secular Modernity (American Journal of Islam and Society, 2016)
The Summer Institute for Scholars 2016, held at the IIIT headquarters in Herndon,VA, from August 8-13, 2016, brought together a group of scholars to address“Islamic Thought and Secular Modernity.” In order to present as manyof their ideas as possible, the wide-ranging and thought-provoking commentsof the chairs and the discussants are not recounted here.